Doctrina del Tribunal Constitucional durante el segundo cuatrimestre de 2013 - Requejo Pagés, Juan Luis; Duque Villanueva, Juan Carlos; Ortega Carballo, Carlos; Ahumada Ruiz, Marian (Revista Española de Derecho Constitucional, 2015)
Sin resumen